2021
DOI: 10.1073/pnas.2106950118
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a complex of apoptosis-inducing factor 1 with cytochrome c oxidase of the mitochondrial respiratory chain

Abstract: Combining mass spectrometry–based chemical cross-linking and complexome profiling, we analyzed the interactome of heart mitochondria. We focused on complexes of oxidative phosphorylation and found that dimeric apoptosis-inducing factor 1 (AIFM1) forms a defined complex with ∼10% of monomeric cytochrome c oxidase (COX) but hardly interacts with respiratory chain supercomplexes. Multiple AIFM1 intercross-links engaging six different COX subunits provided structural restraints to build a detailed atomic model of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…Consistent with the intermembrane space location of the AIF protein (Otera et al , 2005 ), the gene is fused with the C‐terminus of the CG7630 homolog, which is predicted to be in the intermembrane space. Remarkably, a very recent work showed that around 10% of mammalian COX interacts with AIF (Hevler et al , 2021 ). Our findings support the hypothesis that the fusion protein formed by the ortholog of CG7630+AIF, detected in some protostomes, has a functional role, which is carried out in deuterostomes by COX7B interacting with, but physically separated from AIF.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the intermembrane space location of the AIF protein (Otera et al , 2005 ), the gene is fused with the C‐terminus of the CG7630 homolog, which is predicted to be in the intermembrane space. Remarkably, a very recent work showed that around 10% of mammalian COX interacts with AIF (Hevler et al , 2021 ). Our findings support the hypothesis that the fusion protein formed by the ortholog of CG7630+AIF, detected in some protostomes, has a functional role, which is carried out in deuterostomes by COX7B interacting with, but physically separated from AIF.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-linking mass spectrometry (XL-MS) has emerged as a powerful technology for interactome and structural biology studies in mitochondria ( Schweppe et al, 2017 ; Liu et al, 2018 ; Ryl et al, 2020 ; Hevler et al, 2021b ). Chemical cross-linkers react covalently with residues of proteins that are in close proximity to stabilize native PPIs for further characterization ( Gomes and Gozzo, 2010 ; Mintseris and Gygi, 2020 ).…”
Section: Complexome Profiling: Perspectivesmentioning
confidence: 99%
“…It has lately been demonstrated that CP and XL-MS are highly complementary and could provide valuable insights into the macromolecular organization of, for instance, the mitochondrial complexome. By combining CP and XL-MS data, Hevler and co-workers build a detailed atomic model of bovine CIV associated with dimeric apoptosis-inducing factor 1 (AIFM1) ( Hevler et al, 2021b ). CP analysis was indeed helpful to determine the stoichiometry of such a complex and validating this interaction.…”
Section: Complexome Profiling: Perspectivesmentioning
confidence: 99%
“…The apoptosis-inducing factor (AIF) is another proapoptotic factor released from mitochondria and acts as a main effector of its own apoptosis pathway. AIF triggers the apoptosis-related reactions in a caspase-independent manner, and, consequently, its apoptosis pathway is also known as the caspase-independent pathway [ 58 ].…”
Section: Cytomegalovirus Suppresses Apoptosis In Cancer Cellsmentioning
confidence: 99%